(untitled) (Research, Society and Development, 2022)
The larvicidal effect of the essential oil nanoemulsions of Curcuma xanthorrhiza (known as ginger java) in Aedes aegypti species. For this, they were collected as plants of C. xanthorrhiza Luís, MA and, later, separated as leaves from their respective branches. The essential oil was obtained by means of hydrodistillation by dragging a steam at a temperature of 100ºC for 3 hours. The nanoemulsions were prepared using the phase inversion method. The chemical constituents were quantified and identified by Gas Chromatography Coupled with Mass Spectrometry (GC/MS). Aedes aegypti eggs were transmitted through ovit traps. As Aedes aegypti larvae, they were hatched in mineral water, identified and fed until the 4th instar. For the activity of the activity. living and dead count. A Probit statistical analysis was performed to quantify the Lethal Concentration 50% (LC50). The GC/MS quantified the major components in the essential oil, namely germacrone (25.46%), xanthorrizole (17.52%) and eucalyptol (11.92%). The larvicidal activity of the essential oil nanoemulsion for Aedes aegypti quantified an LC50 of 25.94 mg. L-1, being defined by the evaluation criterion as active in the control and combat of A. aegypti. The essential nanoemulsion of C. xanthorrhiza has efficient larvicidal activity, so there is a need for further studies of its form of operation and safety for the combat and control of Aedes aegypti larvae.